Protocol of the VICTORIA study: personalized vitamin D supplementation for reducing or preventing fatigue and enhancing quality of life of patients with colorectal tumor - randomized intervention trial - Schöttker, Ben; Kuznia, Sabine; Laetsch, Dana Clarissa; Czock, David; Kopp-Schneider, Annette; Caspari, Reiner; Brenner, Hermann (BMC cancer, 2020)
BackgroundCancer-related fatigue represents one major cause of reduced quality of life in cancer patients and can seriously affect the physical, emotional, and cognitive functioning impeding coping with the disease. Options for effective treatment of cancer-related fatigue are limited, consisting only of non-pharmacologic interventions like physical activity, psychosocial, and mind-body interventions. Recent evidence suggests that vitamin D-3 supplementation might alleviate cancer-related fatigue. However, confirmation in a randomized controlled trial is needed.MethodsIn this multicenter, randomized, double-blind, placebo-controlled trial, 456 colorectal cancer (CRC) patients aged 18years and older are being recruited in three German rehabilitation clinics. Study inclusion requires hospitalization of at least 3 weeks at such a clinic, a diagnosis of non-metastatic CRC (stage I-III), surgical removal of the tumor within the past 9 months, and season-adapted vitamin D insufficiency or deficiency. Eligible patients are randomly assigned to a personalized regimen of vitamin D-3 or placebo for 12weeks. In the intervention group, a loading dose of 20,000 or 40,000IU vitamin D-3 will be administered daily during the first 11days, followed by a maintenance dose of 2000IU daily. Patients will complete questionnaires for secondary outcomes (fatigue subdomains, quality of life and subdomains, depression, functional well-being, and infection frequency). Blood and urine samples will be collected for analyses of safety parameters (hypervitaminosis D, hypercalcemia, hypercalciuria, and renal impairment) and efficacy biomarkers (25-hydroxyvitamin D, HbA(1c), white blood cell count, leukocyte subtype counts, serum C-reactive protein, uric acid, creatinine, triglycerides, total, low- and high-density lipoprotein cholesterol).DiscussionThis trial tests whether a personalized vitamin D-3 dosing regimen reduces or prevents fatigue among non-metastatic CRC patients by treating the underlying vitamin D deficiency/insufficiency. If efficacy can be confirmed, personalized vitamin D-3 supplementation could be used as a tertiary prevention measure in addition to non-pharmacological treatments of cancer-related fatigue in CRC patients. We expect to detect an effect of vitamin D-3 supplementation on secondary outcomes like quality of life, depression, functional well-being, infections, inflammatory biomarkers, diabetes mellitus, and dyslipidemia.Trial registrationEuropean Clinical Trials Database: EudraCT-No: 2019-000502-30, January 21, 2019; German Clinical Trials Register (DRKS): DRKS00019907, April 30, 2019.
Gesehen am 24.09.2020